Determinantes dos índices de rentabilidade: roa, roe, roi - Lima, Vitória de Sousa Santos (2017)
The objective of this study was to list the variables presented in publications with journals classified in Qualis/CAPES A1, A2, B1 and B2 in the area of Management, Public Management, Accounting and Tourism related to Return on Asset (ROA), Return on Equity (ROE) and Return on Investment (ROI). Therefore, the descriptive analysis of the articles was carried out, obtaining as a base the initial sample of 155 articles on the thematic, reduced to 35, with contents related to the determinants of profitability indicators. The variables found in the study were grouped according to similarity: Macroeconomic Variables, Liquidity and Capital Structure, Environmental, Social and Intangible investments, Profitability Levels, and finally several variables without a specific grouping. The study found that there were no studies on ROI. Significant positive relationships were identified between Selic rate, GDP, social investments, environmental, intangible assets, net margin and asset turnover to ROA and / or ROE. And negative when treated about debt level to ROA and inflation to ROE. These findings suggest the need for further research on the subject.